Prevalencia de parásitos en el tracto gastrointestinal de ovinos en la parroquia de Cusubamba, cantón Salcedo, provincia de Cotopaxi. - Silva Cunalata, Ximena Leonor (2021)
This research aimed to determine the prevalence of parasitic species in the sheep gastrointestinal tract to achieve effective sanitary management of the flocks and higher production yields. A random sample of 100 sheep was carried out, which evaluated parameters such as sex, origin, and body condition under the Famacha technique. Fecal samples were collected from each of the ovine measured. In the laboratory analysis, the Helminth ovoscope concentration method was used, in which the different parasitic genera found were observed and recorded for each sample. Descriptive statistical analysis was performed using the Excel 2013 tool to determine the prevalence and relationship using Chi-Square. Studied population results showed that there is a 92% of prevalence of animals which gave positive for some parasitic infestation; the most relevant genera were: Eimeria spp. 51%, Trichuris spp. 25%, Trichostrongylus spp. 17%. According to sex, the prevalence in 70 females was 90% of those positive, while in the 30 males, 96.6% of those are positive. By the origin prevalence, in the three studied sectors, similar values are manifested concerning infestation percentages. In addition, it was detected by measuring the body condition that 50% of the sheep population is skinny and through the Famacha technique that 51% have slightly anemic mucous membranes. Therefore, it was shown that whole town producers have little knowledge of sheep technical management. Thus, sheep nutritional and sanitary management have enough deficiencies, and they do not understand the negative impact of parasites prevalence in the herds.